Community Based Tourism in The Development of Sustainable Tourism in Baubau City - Salma; Andy Arya Maulana Wijaya; Muh. Askal Basir; Herman Lawelai (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
The purpose of this research is to find out Community Based Tourism in Sustainable Tourism Development in Baubau City. The type of research used in this research is descriptive research with a qualitative approach. The results of this study indicate that Community-Based Tourism Development is to involve the community as in the development planning deliberation process, where the government and the community are together in managing tourism objects. In addition, tourism awareness groups also receive benefits from tourism activities by increasing the economy from tourism activities in Baubau City. Ensuring Environmental Sustainability is to ensure the sustainability of the environment so that it is not damaged or polluted, it is necessary for the role of the government, NGOs, and the community not to damage the physical environment at tourist sites. In addition, providing support both in the form of materials and policies such as providing character education counseling is an effort made in maintaining local character and culture in tourism areas in Baubau City.